(untitled) (Gestión y Gerencia, 2020)
In the present investigation, the main elements of the Venezuelan idiosyncrasy and economic performance were defined; the link between the way Venezuelan society works (idiosyncrasy) and economic progress was demonstrated, as well as the determination of the incidence level that the former has over the latter. It is estimated that only 10% of the population has the capacity to achieve and, therefore, to add value to the nation, which exposes this fact as decisive for entrepreneurship and development. An explanatory, documentary and analysis methodology of 15 years (with a retrospective of 95 years) was applied to a triangulation that obeys to the creation of a causal transmission scheme and to the elaboration of two composite indicators. The results observed focus on the relevance that has generated the anchorage of the idiosyncratic profile of the Venezuelan for the country